Análisis jurídico para determinar la viabilidad del divorcio incausado en la Legislación Ecuatoriana - Garzón Benalcázar, Monserrath Tatiana (2024)
In this scientific article, the objective was based on determining the viability of uncaused divorce by analyzing the legal regulations of other countries and Ecuador. This scientific article used the qualitative-quantitative approach as methodology, with a non-experimental design for the quantitative modality and a narrative design for the qualitative modality, as well as a legal-descriptive scope. The theoretical level methods used were inductive-deductive, historical-logical and analytical-synthetic, and the empirical level methods used were the interview with its tool, the interview guide, and the survey with its respective instrument, the questionnaire. The results obtained showed a notable displeasure among people regarding the length of the divorce process and a dislike due to the high financial costs that it entails. This study concluded that the State has the obligation to guarantee the right to the free development of personality and therefore it is feasible to implement no-fault divorce in Ecuador through a reform to the Civil Code.